2022
DOI: 10.3389/fendo.2022.742474
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Obesity and Cognitive Function in Chinese Elderly Patients With Chronic Schizophrenia

Abstract: BackgroundIt is well known that schizophrenia is associated with sex differences. However, no study has explored the sex differences in obesity and cognitive function in elderly Chinese patients with schizophrenia.ObjectiveThis study aimed to compare sex differences in obesity and cognitive function in elderly Chinese individuals with schizophrenia.MethodsA total of 304 elderly patients with schizophrenia and 130 sex- and age-matched healthy controls from the community were recruited. Demographic, clinical, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Our study supports previous findings that patients with schizophrenia exhibit significant cognitive impairment compared to healthy controls. 23 However, we did not observe any sex differences in the degree of cognitive impairment in patients, which is consistent with the results reported by Zanelli et al 24 and Kao et al 25 Actually, although many studies relying on neuropsychological battery 17,[26][27][28][29] and neuroimaging [30][31][32] have examined the impact of sex on cognitive function in schizophrenia, the conclusion remains controversial. These inconsistencies may be attributed to differences in symptomatology, medication status, illness onset, and illness duration between studies.…”
Section: Discussionsupporting
confidence: 90%
“…Our study supports previous findings that patients with schizophrenia exhibit significant cognitive impairment compared to healthy controls. 23 However, we did not observe any sex differences in the degree of cognitive impairment in patients, which is consistent with the results reported by Zanelli et al 24 and Kao et al 25 Actually, although many studies relying on neuropsychological battery 17,[26][27][28][29] and neuroimaging [30][31][32] have examined the impact of sex on cognitive function in schizophrenia, the conclusion remains controversial. These inconsistencies may be attributed to differences in symptomatology, medication status, illness onset, and illness duration between studies.…”
Section: Discussionsupporting
confidence: 90%
“…Li et al. found that among elderly patients with schizophrenia, obesity rates were 11.7% in men and 21.3% in women, which were significantly higher than in control older adults (6.7% for men and 15.7% for women) (Li et al., 2022). Several studies have found that obese individuals (BMI ≥30 kg/m 2 ) have a higher risk of suicide (Pompili et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of further multiple regression, our study found an association between BMI and suicide risk, showing that the higher the BMI, the higher the risk of suicide. Li et al found that among elderly patients with schizophrenia, obesity rates were 11.7% in men and 21.3% in women, which were significantly higher than in control older adults (6.7% for men and 15.7% for women) (Li et al, 2022). Several studies have found that obese individuals (BMI ≥30 kg/m 2 ) have a higher risk of suicide (Pompili et al, 2006).…”
Section: F I G U R Ementioning
confidence: 99%